Performa Pertumbuhan Larva Ikan Jelawat (Leptobarbus hoevenii Blkr) Yang Dipelihara Dengan Ketinggian Air Berbeda - Burrahman, Inal; Ghofur, Muarofah; Arifin, M Yusuf (Universitas Batangahari Jambi, 2024)
The unusual body shape of jelawat fish fry can inhibit growth due to limited foraging movements and increases the risk of being preyed upon by healthier fry (cannibalism). This abnormality problem is usually only discovered when the seeds are around 1-2 months old. Increasing water levels can speed up the use of energy for finding food and breathing, causing more of the available energy to be used for movement rather than growth. This inhibits bone formation and body growth, causing abnormal fish growth. The aim of this research is to determine the optimal water level to increase the growth of jelawat fish seeds (L. hoevenii Blkr). This research used a Completely Randomized Design (CRD) with 4 different Water Height Treatments (A = 15cm; B = 20cm; C = 25cm; D = 30cm), and each treatment was repeated 3 times. The results of the research showed that water level had a significant effect on the growth of jelawat fish seeds. The optimal water height is 25 cm, with an abnormality rate of 1.05%, absolute length growth reaching 3.15 cm per fish, absolute weight growth of 0.55 grams per fish, and survival rate of catfish fry reaching 99.5%.